MULTI-SCALE ANALYSES ON FLASH FLOOD SUSCEPTIBILITY ASSESSMENT BY USING GEOMORPHOLOGICAL APPROACH AND HYDROLOGICAL MODEL IN JUWANA CATCHMENT, CENTRAL JAVA PROVINCE - , PRIMANDA KIKY W. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Flash flood has become one of the most exposed hazards in Juwana Catchment. It causes destruction to houses and bridges, paddy fields, and even casualties. It becomes important to know the susceptible area of flash flood. Flash flood occurence is mainly controlled by two main factors, i.e. rough topography and heavy rainfall. Therefore, two methods were used to assess the flash flood: by using geomorphological approach and hydrological model. Geomorphological approach includes the quantitative parameters: Relative Height Differences â Slope â Drainage Density